Gaya Komunikasi Curip Almahdi dalam Mengendors Produk di Media Sosial TikTok - Lestiayuaningsih Lestiayuaningsih; Penmardianto Penmardianto (Lembaga Yasin AlSys, 2026)
The phenomenon of social media use, particularly TikTok, has attracted attention in various studies, but research that specifically discusses creators’ communication styles in endorsement activities, especially in local contexts such as Padang City, remains limited. This study aims to analyze Curip Almahdi’s communication style in endorsing products on TikTok social media and to understand its influence on audience responses. This study employed a qualitative approach with a case study design, involving a number of informants consisting of the creator, business actors, and audiences selected through purposive sampling. Data were collected through in-depth interviews, observation of TikTok content, and documentation, and were then analyzed using thematic analysis techniques. The results showed that the communication style used was interpersonal, relaxed, open, and expressive, thereby creating emotional closeness and increasing audience engagement. In addition, the dominance of endorsement content, which reached around 70%, accompanied by high audience interaction, indicates that communication style plays an important role in the effectiveness of delivering promotional messages. These findings contribute to the development of communication style theory and interpersonal communication in the context of digital media, as well as broadening understanding of endorsement practices on social media. The conclusion of this study affirms the importance of an authentic and communicative style in enhancing the effectiveness of digital promotion, and implies the need for content creators and business actors to develop communication strategies that are more adaptive and creative. This study also opens opportunities for further research on the relationship between communication style and consumer behavior on social media.